2021
DOI: 10.3389/fmed.2021.759848
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Engagement in Competency Framework Development in Health Professions: A Systematic Review

Abstract: Competency framework development in health professions has downstream implications for all relevant stakeholders, from the professionals themselves, to organisations, and most importantly end users of services. However, there is little guidance related to what stakeholders might be involved in the competency development process, and when. This review aimed to systematically review literature related to competency framework development methodology in health, to identify the breadth and purpose of key stakeholde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 89 publications
1
18
0
Order By: Relevance
“…Competency frameworks typically describe professional expectations of healthcare professionals by defining the perceived knowledge, skills, attitudes and other characteristics required to practice safely and effectively (1). They translate professional practice to activities such as assessment, curriculum design and educational frameworks, professional regulation, and clinical specialization (1)(2)(3)(4). Despite this central role they play in developing and regulating professional practice (4), standardized approaches to developing competency frameworks are lacking (5).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Competency frameworks typically describe professional expectations of healthcare professionals by defining the perceived knowledge, skills, attitudes and other characteristics required to practice safely and effectively (1). They translate professional practice to activities such as assessment, curriculum design and educational frameworks, professional regulation, and clinical specialization (1)(2)(3)(4). Despite this central role they play in developing and regulating professional practice (4), standardized approaches to developing competency frameworks are lacking (5).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this central role they play in developing and regulating professional practice ( 4 ), standardized approaches to developing competency frameworks are lacking ( 5 ). Uncertainty exists regarding which stakeholders to involve and for what purposes during the development of competency frameworks for health professions ( 2 ). A recent scoping review found significant variation in methodological approaches to competency framework development; a single, internationally recognized standard was not identified ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the article, Making Prospective Entrustment Decisions: Knowing Limits, Seeking Help, and Defaulting, Schumacher et al 3 4 To implement with fidelity, CCCs are meant to review high-quality data from a program of assessment, interrogate this data and follow best practices in group decision making to inform defensible decisions about trainee progress and individualised resident learning plans to facilitate trainee progression towards competence. 5 As such, in CBME, the program of assessment (actioned via CCC's) is intended to serve two purposes: assessment of learning and assessment for learning.…”
Section: Matt Sibbaldmentioning
confidence: 99%
“…This is understandable when considering how these EPA frameworks are generated. Lepre et al 3 identified a sameness to the stakeholder consultation processes in generating EPA frameworks. Most consulted were practitioners and academics, with less than one in five involving those with other workplace perspectives such as service users, policy makers, practitioners from another profession and students.…”
mentioning
confidence: 99%